Pacaran, Motivasi dan Prestasi Belajar Siswa; Apakah Berhubungan? - Rosif, Rosif (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to analyze the relationship between dating as a motivation and academic achievement among students at Antariksa High School, Surabaya. Dating, often perceived as a negative phenomenon, is examined in this research from a positive perspective, specifically as a motivational factor in students' academic achievement. The research method employed is a descriptive quantitative approach with a causal-comparative design. The study's sample consists of 30 second-grade students at Antariksa High School, Surabaya. Data were collected through questionnaires and interviews to identify the reasons behind students' involvement in dating and how it influences their academic performance. The analysis results, using the product-moment correlation, indicate that dating, when done with the purpose of studying together or as a discussion companion, positively contributes to students' academic achievement. Dating was also found to serve as an additional motivation for students to study harder. However, dating solely for maintaining social prestige or following trends tends to have no significant impact on academic performance. Thus, dating can be considered a motivational factor in improving students' academic achievement when directed towards positive goals